Establishment of institutional diagnostic reference level for CT dose on 160 slicer CT scan at Lady Reading hospital Peshawar - Muhammad Imran Khan; Muhammad Zeeshan Khan; Afzal, Fariha; Zenab; Shandana Khan (Journal of the Pakistan Medical Association, 2023)
Objective: To set institutional diagnostic reference level for computed tomography of multiple anatomical regions using dose length product as dosimeter parameter and to compare results with international diagnostic reference level. Method: The retrospective study was conducted at the Radiology Unit of Lady Reading Hospital, Peshawar, Pakistan, and comprised dose data of patients who underwent computed tomography from June 1 to August 31, 2018. The mean, 25th, 50th and 75th percentile of dose distribution of common computed tomography examinations was calculated and compared with other established diagnostic reference levels. Data was analysed using SPSS 20. Results: Of the 1001 scans, 143(14.2%) related to brain, 275(27.5%) abdomen-pelvis, 133(13.3%) kidney-ureter-bladder, 186(18.58%) thorax, 85(8.49%) triphasic, 126(12.58%) musculoskeletal, and 53(5.29%) cardiac. Institutional diagnostic reference levels for the computed tomography unit was established as 50th percentile of dose length product for different regions brain 339, abdomen-pelvis 298, thorax 165, kidney-ureter-bladder 302, triphasic 633, musculoskeletal 366 and cardiac 403. Both 50th and 75th percentile values of dose length product for each individual body region was lower than international Diagnostic reference levels. Conclusion: The diagnostic reference level will be used in routine computed tomography practice at the institution, and will act as the baseline for developing the national diagnostic reference levels. Key Words: CT dose, Dose-length product, Diagnostic reference level, Institutional DRL, National DRL.